Pengaruh Penerapan Nilai-Nilai Islami Dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi pada Bank BSA Cabang Lawang) - Widiana Lendia Imanun Nikmah; Abdul Kodir Djaelani; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis research was conducted at Bank BSA (BPR Sum Adiyatra) Malang Branch. The purpose of this study is to examine and analyze the effect of the application of Islamic values and work environment on the performance of employees of Bank BSA Malang Branch. The variable used is the application of Islamic values and work environment as an independent variable, while the employee performance variable as the dependent variable. The sample used in this study was 40 employees of Bank BSA Malang Branch. The study uses descriptive statistical analysis and inferential statistics. Data collection method by collecting primary data. The analysis used includes the testing of instruments, the classical assumption test, normality test, multiple linear regression and hypothesis testing using multiple regression analysis. The results showed that the variable implementation of Islamic values significantly influenced the performance of Bank BSA Malang Branch employees, while the work environment variable did not significantly influence the performance of Bank BSA Branch Malang employees. Keywords:  application of Islamic values, work environment and employee performance.